Assessment of antibodies to double-stranded DNA induced in rheumatoid arthritis patients following treatment with infliximab, a monoclonal antibody to tumor necrosis factor alpha: findings in open-label and randomized placebo-controlled trials. - Charles, P; Smeenk, R; De Jong, J; Feldmann, M; Maini, R (2000)
OBJECTIVE: To compare the incidence of anti-double-stranded DNA (anti-dsDNA) antibodies in rheumatoid arthritis (RA) patients receiving either single or multiple doses of a chimeric anti-tumor necrosis factor alpha (anti-TNFalpha) antibody or placebo infusions, with or without methotrexate, in open-label, randomized, placebo-controlled trials. METHODS: Multiple sera obtained from 156 patients before and after treatment with infliximab and from 37 patients treated with placebo infusions were tested for anti-dsDNA antibodies by 3 methods: Crithidia luciliae indirect immunofluorescence test (CLIFT), a commercial Farr assay (Ortho Diagnostics radioimmunoassay [RIA]) in which the antigen source is mammalian DNA, and a Farr assay employing 125I-labeled circular plasmid DNA (Central Laboratory of The Netherlands Red Cross Blood Transfusion Service [CLB] RIA). Patients with positive findings on the CLIFT were also tested for antibodies to histones (H1-H5) and chromatin and for IgM rheumatoid factors (IgM-RFs). RESULTS: None of the RA patients had a serum sample that was positive for anti-dsDNA antibodies by the CLIFT prior to infliximab therapy. Of the 22 patients who developed a positive CLIFT result, 11 (7% of 156 exposed to infliximab) also had positive findings on the Ortho RIA at a concentration of >10 units/ml and another 8 (5%) were positive at a concentration of >25 units/ml. In all but 1 patient, the anti-dsDNA antibodies were solely of the IgM isotype. Only 1 patient had detectable anti-dsDNA antibodies by the CLB RIA. All sera containing anti-dsDNA by the CLIFT contained antibodies to chromatin, and sera from 2 patients also contained antibodies to histones. IgM-RF titers showed a significant reduction following infliximab therapy in these 22 patients. One patient developed anti-dsDNA antibodies of IgG, IgA, and IgM isotype and had positive results on both Farr assays (peaking at 22 weeks and resolving by 54 weeks); this was associated with a reversible lupus syndrome. CONCLUSION: Anti-dsDNA antibodies of IgM class are induced by infliximab therapy; the frequency is dependent on the assay method used. Only 1 of the 156 patients who were treated with infliximab developed a self-limiting clinical lupus syndrome; that patient developed high titers of anti-dsDNA antibodies of IgG, IgM, and IgA class, as detected by the CLIFT and by 2 different Farr assays.